Effectiveness of Breadfruit Leaf Extract (Artocarpus Altilis) as a Mouthwash to Reduce Saliva Viscosity - Wiworo Haryani; Siti Hidayati; Lusi Khasanah (JURNAL INFO KESEHATAN, 2020)
Saliva is a complex liquid in the mouth that has an important role as self-cleansing. If the viscosity of saliva is getting lower, the possibility of caries will decrease. The use of mouth rinses is one way to maintain oral hygiene. One of the herbs that can be used as medicine is breadfruit leaf (Artocarpus Altilis). The objective of this study is to determine the effect of breadfruit leaf extract (Artocarpus Altilis) as a mouthwash on saliva viscosity in boarding students of the Dental Nursing Department. This type of research is a pre-experiment with the design of One Group Pretest Posttest which was conducted in October-November 2019. The population of this research study was the boarding students of the Dental Nursing Department of the Yogyakarta Health Polytechnic Ministry of Health with a sample size of 40 respondents taken by purposive sampling technique. Data analysis used Paired Sample T-Test and Simple Linear Regression. 62.5% of respondents aged 18 years with female sex were more than men that were 97.5%. The parametric test results using the Paired Sample T-Test showed a significant difference with a value of p=0.000. Simple Linear Regression analysis test results showed that there was a significant influence between the accumulation of salivary viscosity before and after gargling the breadfruit leaf extract (Artocarpus Altilis) concentration of 20%, with a decrease in the means before gargling the breadfruit leaf extract 3.5810 to 2.6025 with a significance value 0.004 (P<0.05). The conclusion of this study is that there is an influence of breadfruit leaf extract (Artocarpus Altilis) as a mouthwash on saliva viscosity in boarding students of the Dental Nursing Department. It is recommended for further research on the use of breadfruit leaf extract (Artocarpus Altilis) as a mouthwash with different concentrations and solvents so as to increase knowledge of the effectiveness of breadfruit leaves as a mouthwash ingredient.